Effect of physical training on parathyroid hormone and bone turnover marker profile in relation to vitamin D supplementation in soccer players - Brzeziański, Michał; Migdalska-Sęk, Monika; Stuss, Michał; Jastrzębski, Zbigniew; Radzimiński, Łukasz; Brzeziańska-Lasota, Ewa; Sewerynek, Ewa (Biology of Sport, 2022)
The aim of the study was to assess the impact of vitamin D supplementation and regular physical activity on 25-hydroxyvitamin D [25(OH)D], parathyroid hormone (PTH) and bone turnover marker concentrations in healthy male athletes. Twenty-five youth soccer players were divided into groups: non-supplemented (GN) and supplemented (GS) with a vitamin D dose of 20 000 IU twice a week for 8 weeks. The study was conducted during an 8-week preseason period, from mid-January to mid-March. At baseline (T1) and at the end of this period (T2), the serum concentrations of 25(OH)D, (PTH), osteocalcin (OC) and β-isomerized C-terminal telopeptide of type I collagen (β-CTx) were measured. At T2, 25(OH)D increased by 70% in GS (p = 0.004) and by 6% in GN (p > 0.05). Significant differences between GS and GN groups were observed throughout the study in the group-by-time interaction and changes of 25(OH)D (p = 0.002; η2p = 0.36) and OC (p = 0.008; η2p = 0.26). Increased OC (ES = 0.74; moderate) and β-CTx (ES = 1.31, large) in GN athletes who had an optimal baseline vitamin D level (GO) were observed. In GN, at T2, β-CTx positively correlated with PTH and OC (p = 0.007 and p = 0.002). In GS, β-CTx positively correlated with OC at both time points (T1, p = 0.027 and T2, p = 0.037). A negative correlation between 25(OH)D and PTH was observed at T2 (p = 0.018). The obtained results suggest that the 20 000 IU vitamin D3 dose applied twice a week for 8 weeks is effective for vitamin D compensation and sufficient to maintain the correct PTH concentration, as revealed by changes in the bone marker concentrations. In conclusion, the results suggest that the applied vitamin D supplementation dose in athletes leads to intensive bone remodelling and has protective effects on bone under intensive physical effort.